54.8k views
1 vote
−f+2+4f=8−3f what is the answer

User Suli
by
5.8k points

2 Answers

2 votes


-f+2+4f=8-3f\ \ \ \ |\text{use commutative property: a + b = b + a}\\\\-f+3f+2=8-3f\\\\2f+2=8-3f\ \ \ \ |\text{subtract 2 from both sides}\\\\2f=6-3f\ \ \ \ |\text{add 3f to both sides}\\\\5f=6\ \ \ \ \ \ |\text{divide both sides by 5}\\\\f=(6)/(5)\to f=1.2

User Desirae
by
5.4k points
6 votes

1 Simplify -f+2+4f−f+2+4f to 3f+23f+2

3f+2=8-3f3f+2=8−3f

2 Subtract 22 from both sides

3f=8-3f-23f=8−3f−2

3 Simplify 8-3f-28−3f−2 to -3f+6−3f+6

3f=-3f+63f=−3f+6

4 Add 3f3f to both sides

3f+3f=63f+3f=6

5 Simplify 3f+3f3f+3f to 6f6f

6f=66f=6

6 Divide both sides by 66

f=1

User Jamie Burns
by
5.5k points